Development of Module Teaching Materials with the Theme of the Bangkalan Cakraningrat Museum at IPAS Class IV SDN Banyuajuh 02 - Aisyah, Siti; Setyawan, Agung; Mu'ammar (Citra Dharma Cindekia, 2024)
The purpose of this development research is to determine the validity, practicality and effectiveness of the Cakraningrat Bangkalan Museum module teaching materials for grade IV of SDN Banyuajuh 2. This research was conducted in grade IV of SDN Banyuajuh 2. This development research uses data collection techniques such as observation, interviews and questionnaires. This research and development uses the ADDIE model with the stages of Analyze, Design, Development, Implementation, and Evaluation. The validity of the teaching materials of the Cakraningrat Museum Bangkalan module was obtained from the validation of teaching materials experts 77.3% with a valid category, material and language experts 84% with a very valid category and learning design experts 94.6% with a very valid category. The practicality of the teaching materials of the Cakraningrat Museum Bangkalan module was measured using the results of the teacher response questionnaire and the student response questionnaire. The teacher response questionnaire obtained a percentage of 98% and the student response questionnaire obtained a percentage of 91.9% with a very practical category. The effectiveness of the teaching materials of the Cakraningrat Museum Bangkalan module was measured from teacher activity obtaining a percentage of 100% and student activity obtaining a percentage of 98.3% and student learning completeness obtaining a percentage of 90% with a complete category. Based on the results of the study, the teaching materials of the Cakraningrat Museum Bangkalan module were declared valid, practical, and effective so that they are suitable for use in learning science for Class IV SDN Banyuajuh 2